ORGANISATIONAL CULTURE, GOALS AND VALUES: THE PERSPECTIVE OF STAFF MEMBERS OF ORGANISATIONS DELIVERING SOCIAL SERVICES FOR OLDER PEOPLE - NAUJANIENĖ Rasa; MOTIEČIENĖ Roberta; MAŽEIKIENĖ Natalija; VARŽINSKIENĖ Laura; RUŠKUS, Jonas (Socialinė teorija, empirija, politika ir praktika, 2016)
The article presents findings of a case study implemented in the organisations that deliver social services for older people. The aim of the study was to identify and to strengthen psychosocial aspects and commercialisation for effective functioning and development of social services organisations. Results from the case study as part of participatory action research are discussed in the article with the aim to discuss the aspects of organisational culture and values in elderly care organisations. The definition and typologies of organisational culture is presented as theoretical framework for the article emphasising the constructive nature of organisational culture. The case study strategy was used to implement studies in organisations. The first case was composed of two public organisations that provide care for older persons at his/her own home. The second case was composed of two profit organisations that provide institutional care for older persons. 43 staff members from managers to care workers participated in the case study. Based on the results of the case study, it is discussed how managers and employees in their reflected stories talk about organisation’s mission and goals. Based on these stories, researchers disclosed different aspects of organisational culture and values. Public organisations are focused on service delivery in order to keep clients at home as long as possible in order to avoid stationary services. Care, communication and collaboration are related with organisational culture in public organsations. While profit organisations are focused on the market and its dictated terms such as accountability, financial effectiveness and etc. The study allowed to identify organisational culture in public organisations based on Hofstede typology where domination of female and strong uncertainty avoidance culture was visible. In profit organisations the balance between female and male cultural dimensions was recognised.